HST WFC3/Grism observations of the candidate ultra-high-redshift radio galaxy GLEAM J0917–0012. (12th April 2022) - Seymour, N.; Drouart, G.; Noirot, G.; Broderick, J. W.; Turner, R. J.; Shabala, S. S.; Stern, D. K.; Bellstedt, S.; Driver, S.; Davies, L.; De Breuck, C. A.; Afonso, J. A.; et al.
Abstract: We present Hubble Space Telescope Wide Field Camera 3 photometric and grism observations of the candidate ultra-high-redshift ( $z>7$ ) radio galaxy, GLEAM J0917–0012. This radio source was selected due to the curvature in its 70–230 MHz, low-frequency Murchison Widefield Array radio spectrum and its faintness in K -band. Follow-up spectroscopic observations of this source with the Jansky Very Large Array and Atacama Large Millimetre Array were inconclusive as to its redshift. Our F105W and F0986M imaging observations detect the host of GLEAM J0917–0012 and a companion galaxy, $\sim$ one arcsec away. The G102 grism observations reveal a single weak line in each of the spectra of the host and the companion. To help identify these lines we utilised several photometric redshift techniques including template fitting to the grism spectra, fitting the ultraviolet (UV)-to-radio photometry with galaxy templates plus a synchrotron model, fitting of the UV-to-near-infrared photometry with EAZY, and fitting the radio data alone with RAiSERed . For the host of GLEAM J0917–0012 we find a line at $1.12\, μ$ m and the UV-to-radio spectral energy distribution (SED) fitting favours solutions at $z\sim 2$ or $z\sim 8$ . While this fitting shows a weak preference for the lower redshift solution, the models from the higher redshift solution are more consistent with the strength of the spectral line. The redshift constraint by RAiSERed of $>6.5$ also supports the interpretation that this line could be Lyman $-α$ at $z=8.21$ ; however EAZY favours the $z\sim 2$ solution. We discuss the implications of both solutions. For the companion galaxy we find a line at $0.98\, μ$ m and the SED fitting favours solutions at $z<3$ implying that the line could be the [OII] $λ3727$ doublet at $z=1.63$ (although the EAZY solution is $z\sim 2.6± 0.5$ ). Further observations are still required to unambiguously determine the redshift of this intriguing candidate ultra-high-redshift radio galaxy.